Context and proposal of the scope of family action - Balabarca Cardenas, Yván (2018)
This article aims to give a review of the macro social movements that impacted the family in the nineteenth and twentieth centuries; the adaptation of the family to these tendencies; and, the proposal of the scope of action of the Adventist family at this time.